Nunavut Inuit youth and leadership: Perspectives from the Northern Youth Abroad Program - Aylward, Erin; Giles, Audrey; Abu-Zahra, Nadia (Études/Inuit/Studies, 2013)
AbstractNorthern Youth Abroad (NYA) is the first and presently the only educational travel program developed specifically to meet the needs of the Canadian North’s youth. Part of NYA’s mandate, cultivating northern youth leadership, has received very little academic attention and merits greater investigation. In this qualitative case study, we draw on semi-structured interviews with 10 Nunavut Inuit past participants, one NYA staff member, and one NYA Board member, as well as archival research at NYA. We argue that NYA alumni use both traditional Inuit and Euro-Canadian approaches to leadership development; as a result, these youths have created what Bhabha described as a “third space,” where the binary dynamic between colonial/neo-colonial and traditional influences is displaced by new structures that weave heterogeneous influences together. These findings suggest that NYA’s Nunavut Inuit alumni possess strong and adaptive leadership abilities. We conclude that in order to better understand the challenges that face the current generation of Inuit youths, researchers should be well advised to recognise the adaptability, resilience, and leadership that Nunavut Inuit youths such as NYA alumni have developed and use in a wide variety of areas of their lives.